Needs Analysis for Educational Comic Media as a Learning Tool in Elementary Schools - Yulianti, Maulida Rizka; Usman, Herlina; Yunus, Mahmud (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2025)
Technological advancements have driven innovation in learning media; however, their utilization at the elementary school level remains limited. Several institutions lack media that aligns with the characteristics and needs of fifth-grade students. The absence of media that integrate visual and narrative elements hinders the improvement of student motivation and comprehension. Therefore, a needs analysis of educational comic press as a practical learning tool in elementary schools is necessary. This study employs a descriptive qualitative approach to examine the need for educational comic media in elementary education through observation, interviews, and document analysis. Data analysis employs Miles and Huberman’s interactive model, which involves data reduction, display, and verification, with validity reinforced through triangulation. Findings indicate the need for innovative learning media suited to students’ developmental stages and learning contexts. The results show that digital comics have a strong potential to enhance student interest and engagement. Combining visual and textual elements makes the material more accessible, especially for visual learners. Digital comics are also effective for character education. However, successful implementation requires infrastructure support and teacher training. Collaboration between teachers and parents is essential to create inclusive, engaging learning that meets 21st-century educational needs. This research expands learning media alternatives by proposing digital comics as practical tools for improving reading interest, material comprehension, and character education. It also highlights the importance of teacher-parent collaboration and the need for training and infrastructure in the digital era.